NSCLC molecular testing in Central and Eastern European countries - Ryska, Ales; Berzinec, Peter; Brcic, Luka; Cufer, Tanja; Dziadziuszko, Rafal; Gottfried, Maya; Kovalszky, Ilona; Olszewski, Włodzimierz; Oz, Buge; Plank, Lukas; Timar, Jozsef (BMC cancer, 2018)
BACKGROUND: The introduction of targeted treatments for subsets of non-small cell lung cancer (NSCLC) has highlighted the importance of accurate molecular diagnosis to determine if an actionable genetic alteration is present. Few data are available for Central and Eastern Europe (CEE) on mutation rates, testing rates, and compliance with testing guidelines. METHODS: A questionnaire about molecular testing and NSCLC management was distributed to relevant specialists in nine CEE countries, and pathologists were asked to provide the results of EGFR and ALK testing over a 1-year period. RESULTS: A very high proportion of lung cancer cases are confirmed histologically/cytologically (75-100%), and molecular testing of NSCLC samples has been established in all evaluated CEE countries in 2014. Most countries follow national or international guidelines on which patients to test for EGFR mutations and ALK rearrangements. In most centers at that time, testing was undertaken on request of the clinician rather than on the preferred reflex basis. Immunohistochemistry, followed by fluorescent in situ hybridization confirmation of positive cases, has been widely adopted for ALK testing in the region. Limited reimbursement is a significant barrier to molecular testing in the region and a disincentive to reflex testing. Multidisciplinary tumor boards are established in most of the countries and centers, with 75-100% of cases being discussed at a multidisciplinary tumor board at specialized centers. CONCLUSIONS: Molecular testing is established throughout the CEE region, but improved and unbiased reimbursement remains a major challenge for the future. Increasing the number of patients reviewed by multidisciplinary boards outside of major centers and access to targeted therapy based on the result of molecular testing are other major challenges.
Keywords: Molecular testing; Carcinoma, Non-Small-Cell Lung; Evropa; Europe; Non-small cell lung cancer; Mutation; genová přestavba; nádorové biomarkery; Central eastern European region; Gene Rearrangement; ALK rearrangements; Humans; Biomarkers, Tumor; prognóza; Prognosis; Lung Neoplasms; nemalobuněčný karcinom plic; genetické testování; EGFR mutations; mutace; lidé; nádory plic; Genetic Testing